Prevalência das lesões precursoras de câncer de colo uterino nas adolescentes e jovens da Amazônia - Arcoverde, Luciana Cabus (2013)
The present study focused on the investigation of factors related to high rates of lesions considered precursors of Cervical Cancer in Roraima, focusing in particular, on the adolescents and young women population, through analysis of data on the degree of intraepithelial lesion, interval between examinations, education , origin and presence of sexually transmitted diseases, available on the "Viva Mulher" program, in order to assess the epidemiological profile of these women. Intraepithelial lesions were found in 3.6% of smear tests carried out during 2012 in Roraima. The prevalence of abnormal results suggestive of intraepithelial lesions was significantly higher in younger women compared to older (6.03% vs 3.01%, respectively, p = 0, 0013). The prevalence of low-grade squamous intraepithelial lesion was higher in younger patients, and was statistically significant when compared to those with more than 25 years of age (5.27% vs 1.96%, respectively, p <0, 0001). There was no statistically significant difference between the prevalence of high-grade squamous intraepithelial lesion in the group of women under 25 and over 25 years of age (0.75% vs 1.05%, respectively, p = 0.18 .) Despite the fact that the state of Roraima has the largest youth population in the country, and also harbor a indigenous population that correspond to 15% of the total state population, these particular situations were not considered in specific screening programs. Our results suggest the need for modifications and suitability of programs, that includes adolescents and young women, and improve the records of indigenous population.